1999
DOI: 10.1183/09031936.99.13112599
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of pulmonary rehabilitation in patients with chronic airway obstruction

Abstract: The aim of this study was to evaluate the long-term outcome of an outpatient pulmonary rehabilitation programme (PRP) in patients with chronic airway obstruction (CAO).In 61 CAO patients (35 asthmatics and 26 chronic obstructive pulmonary disease (COPD)) lung and respiratory muscle function, exercise tolerance (by symptom limited cycloergometer and walking tests), dyspnoea (Borg scale, visual analogue scale (VAS), baseline and transitional dyspnoea index (BDI and TDI, respectively)) and quality of life (St Geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
107
2
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 37 publications
12
107
2
7
Order By: Relevance
“…However, despite the improvement in walking distance, in our study modified Borg scores did not significantly change between the first and last PR assessment. Most studies that have observed significant improvements in modified Borg Scores following PR have reported higher breathlessness scores at baseline (>5) [14,[22][23][24]. In contrast, the average resting modified Borg Score in this study was found to be very low at baseline (equating to 'very mild shortness of breath'), and remained low after the six week PR programme.…”
Section: Discussioncontrasting
confidence: 54%
“…However, despite the improvement in walking distance, in our study modified Borg scores did not significantly change between the first and last PR assessment. Most studies that have observed significant improvements in modified Borg Scores following PR have reported higher breathlessness scores at baseline (>5) [14,[22][23][24]. In contrast, the average resting modified Borg Score in this study was found to be very low at baseline (equating to 'very mild shortness of breath'), and remained low after the six week PR programme.…”
Section: Discussioncontrasting
confidence: 54%
“…This confirms the results of previous studies [20,21] that showed a significant improvement in hospitalisation rate and hospital stay after pulmonary rehabilitation. Prior studies assessing the long-term effects of PR have reported that gains in health-related quality of life and HCRU, persist for up to 2 yrs following PR, and that other outcomes, such as improvements in dyspnoea and functional capacity, are lost if patients fail to remain active [26,27,36]. In the current study, 29% of PR graduates joined a supervised maintenance exercise programme and continued to exercise (three times per week) throughout their observational period, and as many as 49% of graduates reported that they continued to exercise on a regular basis for at least 1 yr following PR.…”
Section: Discussionmentioning
confidence: 99%
“…While it is well documented that the benefits of multidisciplinary pulmonary rehabilitation gradually decline over 1 or 2 yrs [10][11], the long-term effects of IMT were investigated to a much lesser extent in COPD.…”
mentioning
confidence: 99%